A dictionary of modern American usage - Garner, Bryan A. (New York : Oxford University Press, 1998)
"This wonderfully written work aims to help people use language so they will use the right words to say what they mean. Garner relies on modern sources rather than historical precedent to determine the current, correct usage. He even advises writers about which words to avoid altogether. Each of the approximately 7,000 entries provides a definition, discusses the usage of the word, provides illustrative quotations, and gives citations to the references and quotations. This is an entertaining, witty, and unpretentious resource that will always come in handy in the public or academic library."----"Outstanding reference sources 2000", American Libraries, May 2000. Comp. by the Reference Sources Committee, RUSA, ALA.
Includes bibliographical references (p. [721]-723).
Keywords: English language -- United States -- Usage -- Dictionaries; Americanisms -- Dictionaries